Analisis Lembaga Lingkungan Pendidikan - Nurpitroh, Akhmarina; Aripin, Mochamad (Addabani: Interdisciplinary Journal of Islamic Education, 2023)
Education is the key to the progress of a nation. Developed countries are usually followed by advanced education. To realize competitive education, it must be supported by quality educational institutions. Quality here means having adequate facilities and infrastructure, supporting human resources, a curriculum that is in accordance with the needs or changing times and so on. The government, in this case, must not remain silent in supporting the national education system so that Indonesia is able to compete with other countries with advanced education systems.